A bizalom, mint a környezetbarát termékek fogyasztói elfogadásának kritikus tényezője - Lányi, Beatrix (Közép-Európai Közlemények, 2025)
In recent years environmental issues gained significant interest that has led to an increased awareness of environmentally friendly products. However, trust plays a crucial role, how consumers approach to and adopt these products. Trust serves as the core upon which consumer acceptance of environmentally friendly products is built. Consumers are more likely to choose these products when they feel that they are behaving eco-friendly and sustainable. Trust is multifaceted and can be influenced by various factors, including the credibility of product claims, brand reputation, and transparency in manufacturing processes. One of the most crucial factors influencing trust in environmentally friendly products is the credibility of their environmental claims. Consumers are increasingly analysing product labels and certifications to ascertain their authenticity. Companies that provide clear and transparent information about their products’ environmental attributes foster trust among consumers. Moreover, third-party certifications from reputable organizations serve as a signal of credibility, reassuring consumers of the product’s environmental authorization. This paper gives an overview about the importance of trust in consumers’ acceptance of environmentally friendly products. In-depth interviews were carried out for the deeper analysis to highlight the drivers and disincentives of trust in green products. The possible reasons behind the still moderate level of trust in environmentally friendly products are analyzed and suggestions are formulated how these information barriers could be overcome or eventually be eliminated completely. It is important in the future as trust plays a fundamental role in consumer acceptance of environmentally friendly products. Credibility, brand reputation, and transparency are essential factors shaping consumer trust in these products. As consumer awareness of environmental issues continues to rise, companies must prioritize building and maintaining trust to succeed in the growing market for environmentally friendly products.